2020
DOI: 10.1016/j.heliyon.2020.e05132
|View full text |Cite
|
Sign up to set email alerts
|

Can accelerated transcranial direct current stimulation improve memory functions? An experimental, placebo-controlled study

Abstract: The aim of this study was to investigate whether transcranial Direct Current Stimulation (tDCS) could improve verbal memory functions in healthy old and younger participants. We hypothesized that active tDCS led to significantly improved memory function, compared to placebo tDCS. Forty healthy participants (20 old and 20 younger participants) were included in the study. We applied a novel stimulation protocol, where six sessions of anodal tDCS were administrated during two consecutive days. Each tDCS session l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In a similar study design targeting Parkinson's Disease, Doruk and colleagues ( 66 ) report significant improvements on the TMT-B without changes on the TMT-A, with the maintenance of these findings extending to one-month post-stimulation. Bystad and colleagues ( 67 ) further report significant gains on the TMT-B without improvements in the TMT-A only within a young adult group. In addition, Loftus and colleagues ( 68 ) report reaction time improvements on the Stroop task in young adults after receiving anodal DLPFC stimulation resulting in inhibitory control enhancement; our results continue to support inhibition control enhancement in older aged adults.…”
Section: Discussionmentioning
confidence: 96%
“…In a similar study design targeting Parkinson's Disease, Doruk and colleagues ( 66 ) report significant improvements on the TMT-B without changes on the TMT-A, with the maintenance of these findings extending to one-month post-stimulation. Bystad and colleagues ( 67 ) further report significant gains on the TMT-B without improvements in the TMT-A only within a young adult group. In addition, Loftus and colleagues ( 68 ) report reaction time improvements on the Stroop task in young adults after receiving anodal DLPFC stimulation resulting in inhibitory control enhancement; our results continue to support inhibition control enhancement in older aged adults.…”
Section: Discussionmentioning
confidence: 96%
“…Previously published studies indicate that short repetition interval (<30 min) can lead to prolongation of tDCS after-effects ( 81 83 ), whereas longer repetition interval (3 or 24 h) result in no excitability-enhancing after effects or can nullify them ( 83 , 84 ). Current research focuses on accelerated tDCS protocols ( 85 , 86 ), and future RCT protocols using tDCS as a treatment option for schizophrenia might benefit from their implementation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Monte-Silva et al reported that spacing two tDCS sessions by short intervals of 3 and 20 minutes resulted in long-lasting effects of tDCS on motor cortical excitability with a greater magnitude of effects for the 20-min interval [4], whereas longer intervals, such as 3 or 24 hours, abolished the long-lasting effects of tDCS [4,5]. Thus, the use of short intervals between sessions (<30 min) has been proposed to prolong the effect of tDCS [6]. The clinical potential of such protocols, which can be referred to as "accelerated" or "intensive", is increasingly being investigated with other forms of noninvasive brain stimulation.…”
Section: Dear Editormentioning
confidence: 99%